2020
DOI: 10.18632/aging.103128
|View full text |Cite
|
Sign up to set email alerts
|

Nur77 attenuates inflammatory responses and oxidative stress by inhibiting phosphorylated IκB-α in Parkinson’s disease cell model

Abstract: Neuroinflammation and oxidative stress play key roles in the pathological development of Parkinson's disease (PD). Nerve growth factor-induced gene B (Nur77) is closely related to dopamine neurotransmission, and its pathogenesis is unclear. This study aims to investigate the role and mechanism of Nur77 in a cell model of Parkinson's disease. Silencing Nur77 with siRNA can aggravate intracellular LDH release, increase the expression of pro-inflammatory genes (such as tumor necrosis factor α, nuclear factor κB (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 24 publications
3
12
0
1
Order By: Relevance
“…The inflammatory mediators IL-6, TNF-α, and ICAM-1 cause neuroinflammation and dopaminergic neuronal loss in PD, and are all regulated by a “master switch” for inflammatory gene expression—NF-κB ( 39 ). In the in vitro and in vivo PD models, expression levels of IL-6, TNF-α, p-p65, and MCP-1 were increased ( 40 , 41 ), changes that are found in PD brains as well ( 42 45 ). Previous studies showed that kurarinone, a lavandulyl flavanone from S. flavescens ( 21 ), inhibits iNOS-dependent nitric oxide release, reactive oxygen species generation, and expression of inflammatory cytokines (e.g., TNF-α, IL-1β, and iNOS) in lipopolysaccharide-induced RAW264.7 macrophages ( 24 ), which reveals that kurarinone might possess anti-inflammatory potential in PD.…”
Section: Discussionmentioning
confidence: 98%
“…The inflammatory mediators IL-6, TNF-α, and ICAM-1 cause neuroinflammation and dopaminergic neuronal loss in PD, and are all regulated by a “master switch” for inflammatory gene expression—NF-κB ( 39 ). In the in vitro and in vivo PD models, expression levels of IL-6, TNF-α, p-p65, and MCP-1 were increased ( 40 , 41 ), changes that are found in PD brains as well ( 42 45 ). Previous studies showed that kurarinone, a lavandulyl flavanone from S. flavescens ( 21 ), inhibits iNOS-dependent nitric oxide release, reactive oxygen species generation, and expression of inflammatory cytokines (e.g., TNF-α, IL-1β, and iNOS) in lipopolysaccharide-induced RAW264.7 macrophages ( 24 ), which reveals that kurarinone might possess anti-inflammatory potential in PD.…”
Section: Discussionmentioning
confidence: 98%
“…Although NR4A1 is a so-called orphan receptor for which no natural ligands have yet been identified, synthetic ligands are available and have recently been successfully used in attenuating pro-inflammatory mediators (Cho et al 2007, Zhang et al 2008). Cytosporone-B mediated NR4A1-acitivation has further been shown to ameliorate osteoarthritis by reducing chondrocyte-mediated inflammation (Xiong et al, 2020), to attenuate inflammatory responses in a Parkinson’s disease model (Yan et al, 2020) or even in an experimental model of influenza virus infection via modulation of alveolar macrophages (Egarnes et al, 2017). Indeed, application of Cytosporone-B results in reduced infarcts and improved functional outcome and thus represents a promising future candidate for stroke treatment.…”
Section: Discussionmentioning
confidence: 99%
“…10 In addition, in Nur77 knockout mice, the serum levels of LPS, TNFα and IL-1β were previously shown to be increased significantly. 31 This result mainly showed that the level of inflammation was increased in Nur77 knockout mice. To further clarify whether the increased number of osteoclasts in Nur77 knockout mice was associated with more inflammation, we next measured the levels of inflammation in mouse femurs.…”
Section: Nur77 Deletion Improves Serum Inflammation Levels and Activa...mentioning
confidence: 92%